Quercetin prevents age-related hearing loss in C57BL/6J mice by activating mitophagy and inhibiting the NLRP3 inflammasome - Menglong Feng; Xiaoqing Zhou; Ting Yang; Zhiji Chen; Guijun Yang; Xu Jiang; Wei Yuan (PLoS ONE, 2026)
Objective Age-related hearing loss (ARHL), the most prevalent sensory impairment in older adults, is closely associated with NOD-like receptor thermal protein domain-containing protein 3 (NLRP3) inflammasome activation and mitochondrial dysfunction. Quercetin, a natural flavonoid, shows anti-inflammatory and antioxidant properties, but its role in ARHL remains unclear. In this study, we investigated the protective effects and underlying mechanisms of quercetin on ARHL in a mouse model, focusing on both NLRP3 inflammasome and mitophagy. Materials and methods Quercetin was administered intragastrically to C57BL/6J mice from the age of 6 months to 12 months. The function of the hearing system was evaluated by auditory brainstem response (ABR) and hematoxylin and eosin (HE) staining of the cochlea. The levels of oxidative stress markers were detected using specific kits. Gene expression was detected by quantitative reverse transcripation polymerase chain reaction (qRT-PCR) and Western blot. Results The results showed that quercetin effectively reduced the ABR threshold shift at 8, 16, and 32 kHz frequencies and improved cochlear tissue morphology. It also reduced oxidative stress and inflammatory factors such as tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), interleukin-18 (IL-18), and interleukin-1β (IL-1β), in the cochlea and auditory cortex of C57BL/6J mice. Notably, the activation of the NLRP3 inflammasome was attenuated in the quercetin-treated group, as evidenced by decreased expression of NLRP3, apoptosis-associated speck-like protein (ASC), IL-1β, IL-18, caspase-1 and cleaved caspase-1. Additionally, quercetin treatment promoted the expression of autophagy-related genes in the cochlea and auditory cortex, such as PTEN induced putative kinase 1 (PINK1), Parkinson disease-related protein 2 (PARKIN), BCL2 interacting protein 3 (BNIP3) and microtubule-associated protein 1 light chain 3B (LC3B), and increased the LC3B-II/LC3B-I ratio. Conclusion These findings indicated that quercetin exerted a protective effect against ARHL by suppressing NLRP3 inflammasome activation and modulating mitophagy, providing a theoretical basis for applying quercetin to treat ARHL.